2010
DOI: 10.1111/j.1600-0625.2010.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of metallothionein isoforms is associated with collagen deposition in proliferating keloid fibroblasts in vitro

Abstract: The keloid fibroblast (KF) is known to have higher proliferative capacity than normal dermal fibroblast (NF). Metallothionein (MT), a metal-binding protein, has been reported to promote cell proliferation. In this study, we evaluated the expression of MT isoforms at the mRNA level in fetal bovine serum (FBS)-stimulated proliferating KF. Although the morphological appearance of NF and KF was similar when viewed under light, confocal and transmission electron microscopy, there was surprisingly a generally lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
(59 reference statements)
2
11
1
Order By: Relevance
“…Takano and colleagues demonstrated that transgenic mice with metallothionein overexpression were more resistant to neutrophilic lung inflammation and lung edema induced by intratracheal challenge with LPS (52). Metallothionein-2 has also been found to be a critical regulator of NF-κB signaling because its upregulation attenuates NF-κB activity in tumor cells, keloid fibroblastic cells, as well as cardiomyocyte cells (53)(54)(55)(56). In line with these studies, our results demonstrated the antiinflammatory effects of metallothionein-2 on both macrophages and mouse colitis models.…”
Section: Discussionsupporting
confidence: 87%
“…Takano and colleagues demonstrated that transgenic mice with metallothionein overexpression were more resistant to neutrophilic lung inflammation and lung edema induced by intratracheal challenge with LPS (52). Metallothionein-2 has also been found to be a critical regulator of NF-κB signaling because its upregulation attenuates NF-κB activity in tumor cells, keloid fibroblastic cells, as well as cardiomyocyte cells (53)(54)(55)(56). In line with these studies, our results demonstrated the antiinflammatory effects of metallothionein-2 on both macrophages and mouse colitis models.…”
Section: Discussionsupporting
confidence: 87%
“…Severe hypoxia and malnutrition act as a damaging stimulus, greatly increasing p53 expression and inducing cell cycle arrest and apoptosis . Fu et al (2011) cultured stem cells in vitro under 2% O 2 and serum‐deprived conditions to mimic ischaemic in vivo cartilage conditions . The results demonstrated that these ischaemic, malnourished conditions promoted stem cell apoptosis, and the extent of apoptosis was greater in serum deprivation alone than hypoxia alone .…”
Section: Discussionmentioning
confidence: 99%
“…Cells entering the cell cycle require higher amounts of Zn, whereas most transcription factors required for the transcription of enzymes necessary to initiate DNA synthesis need zinc to form their zinc fingers (Kuppens and De Ley, 2006). Modulation of MT isoforms was also associated with collagen deposition in proliferating keloid fibroblasts in vitro (Toh et al, 2010). It can be concluded that a role of MTs is connected with redox processes (Wlostowski, 1993) and with protection of DNA from oxidative damage (Chubatsu and Meneghini, 1993) in cell proliferation.…”
Section: Proliferationmentioning
confidence: 96%